Background and Resolution of Ethnic Conflict in Myanmar - Sutpanpot, Pracha (Thai Social Science Journal, 2025)
The origin of ethnic conflicts in Myanmar is a result of the history of the nation in the past with cultural and ethnic differences, leading to the inability to reconcile when independence was gained. The struggle to establish a state led to prolonged conflicts, leading to violence from ethnic conflicts. Attempts to resolve ethnic conflicts through the peace process in Myanmar, which began with the current democratic process in Myanmar under bilateral peace agreements from ethnic groups, aim to maintain the stability of the political situation in the country. The important roles of the army, the civilian government, and ethnic groups by the government must be supported by the army in order to be successful. While the army has overlapping interests, even though the new government is democratic, it sends a positive signal to ethnic groups who still have problems in participating. The peace process, although an urgent and important agenda, will only reach an acceptable agreement when the interests of all parties involved converge. How well the problem of the situation will be resolved depends on how much all parties are willing to compromise their positions for the sake of long-term peace and stability.